Transcriptional response of a target plant to benzoxazinoid and diterpene allelochemicals highlights commonalities in detoxification - Eva Knoch; Judit Kovács; Sebastian Deiber; Keisuke Tomita; Reshi Shanmuganathan; Núria Serra Serra; Kazunori Okada; Claude Becker; Niklas Schandry (BMC Plant Biology, 2022)
Abstract Background Plants growing in proximity to other plants are exposed to a variety of metabolites that these neighbors release into the environment. Some species produce allelochemicals to inhibit growth of neighboring plants, which in turn have evolved ways to detoxify these compounds. Results In order to understand how the allelochemical-receiving target plants respond to chemically diverse compounds, we performed whole-genome transcriptome analysis of Arabidopsis thaliana exposed to either the benzoxazinoid derivative 2-amino- 3H-phenoxazin-3-one (APO) or momilactone B. These two allelochemicals belong to two very different compound classes, benzoxazinoids and diterpenes, respectively, produced by different Poaceae crop species. Conclusions Despite their distinct chemical nature, we observed similar molecular responses of A. thaliana to these allelochemicals. In particular, many of the same or closely related genes belonging to the three-phase detoxification pathway were upregulated in both treatments. Further, we observed an overlap between genes upregulated by allelochemicals and those involved in herbicide detoxification. Our findings highlight the overlap in the transcriptional response of a target plant to natural and synthetic phytotoxic compounds and illustrate how herbicide resistance could arise via pathways involved in plant-plant interaction.